Fishmeal replacers: Review of antinutrients within oilseeds and pulses - A limiting factor for the aquafeed Green Revolution? - Tacon A.G.J. (Feeding tomorrow's fish, 1997)
The paper reviews the endogenous antinutritional factors or antinutrients present within plant feedstuffs, and in particular those protein-rich feedstuffs with potential for use as 'fishmeal replacers' within compound aquafeeds. The toxicity of the major antinutritional factors for farmed fish and shrimp are discussed, and information presented concerning the processing and/or biotechnological methods commonly used to destroy or inactivate them.
Workshop of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1996/06/24-26, Mazarrón (Spain)